Environmental impacts of lithium supply chains from Australia to China - Yan Feng; Peng Wang; Wen Li; Qian Zhang; Wei-Qiang Chen; Danyi Feng (Environmental Research Letters)
Lithium (Li) has been widely recognized as an essential metal for clean technologies. However, the environmental impacts and emission reduction pathways of the lithium supply chain have not been clearly investigated, especially between Australia and China, where most lithium ore are mined and produced. This study analyzed and compared the environmental and human health implications of six key cross-border Li supply chains from Australia to China through material flow analysis (MFA) and life cycle assessment (LCA) methods. Key findings include: (1) approximately 30% of total Li extraction is lost in the beneficiation stage due to low recovery rates; (2) the Cattlin–Yaan routes exhibit superior environmental and human health performances than other routes attributed to lower diesel consumption, reduced electricity use, and a high chemical conversion rate; (3) the Wodgina production routes have a higher carbon footprint mainly due to low ore grade and significant diesel consumption; (4) the dominant environmental implications in the supply chain are associated with refining battery-grade lithium carbonate, driven by energy use (electricity, coal and natural gas), sulfuric acid, soda ash, and sodium hydroxide. In addition, lithium carbonate refining has the highest water consumption. Overall, the analysis highlights opportunities to improve environmental performance, advance data-poor environmental assessments, and provide insights into sustainable Li extraction.